Le visite pastorali del vescovo Francesco Zeno nella diocesi di Capodistria (1660-1680) - Vincoletto, Roberta (Annales. Series historia et sociologia, 2008)
This paper emphasises the pastoral work of Francesco Zeno, born in Candia (Crete), but originally from Venice, who was Bishop of the Diocese of Koper from 1660 to 1680. The paper includes the reading and analysis of the five pastoral visits made by Zeno to the Diocese of Koper during his episcopate, a study as well as a comparison with his ad limina report, from which it will be possible to learn about different aspects of the history of the local church and, more generally, of the entire community. The sources used prove that this was a very peaceful diocese, without any particular problems. The Bishop repeatedly and punctually visited it; he paid attention to the problems, and patiently tried to improve the effectiveness of pastoral action
Keywords: 17.st.; koprska škofija; pastoralni obiski; Zeno, Francesco